The Influence Of Ownership Structure On GCG Effectiveness And Its Implications For Financial Performance - Mismiwati Mismiwati (Oikonomia : Journal of Management Economics and Accounting, 2025)
Ownership structure constitutes a fundamental component of corporate governance systems, influencing strategic decision-making processes, power distribution, and the allocation of economic rights within organizations. Variations in ownership composition—managerial, institutional, public, and foreign directly affect internal control and monitoring mechanisms. Significant managerial ownership can align management and shareholder interests, while institutional ownership enhances managerial discipline through superior monitoring capacity. Public ownership promotes information transparency, whereas foreign ownership often introduces international governance standards. Good Corporate Governance (GCG) operates as a formal mechanism to ensure that corporate management adheres to the principles of transparency, accountability, responsibility, independence, and fairness. The synergy between an optimal ownership structure and robust GCG can reduce agency costs, improve operational efficiency, and strengthen corporate reputation and competitiveness. Conversely, weak governance may lead to entrenchment effects, free rider problems, and moral hazard. This study employs a qualitative approach using a systematic literature review to examine the interplay between ownership structure, GCG effectiveness, and financial performance. The findings are expected to provide theoretical contributions by enriching the corporate governance and financial management literature, as well as practical implications for managers and regulators in designing ownership strategies and governance policies that promote sustainable corporate value creation.